Penguasaan Konsep Siswa dalam Pendekatan Interactive Conceptual Instruction(ICI) dengan Video Pembelajaran - Astuti, Dewi; Fauziah, Muna (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2021)
This research aims to analyze mastery of thematic learning concepts in the Interactive Conceptual Instruction approach with learning videos. The sample in this study was 119 grade IV students in four public elementary schools in Laweyan District, Surakarta, Indonesia. Pre-test and post-test forms are used as a measure of students' mastery of concepts. The test instrument used is a concept mastery test. The test results were analyzed qualitatively and quantitatively. The results of the analysis show that learning influences concept mastery in a very strong category. The results of increasing students' mastery of concepts before and after learning are in the low category.